1990
DOI: 10.1080/00029157.1990.10402819
|View full text |Cite
|
Sign up to set email alerts
|

A Hypnotherapeutic Approach to the Improvement of Compliance in Adolescent Diabetics

Abstract: Adolescents with insulin-dependent diabetes mellitus (IDDM) have a rate of noncompliance in our clinic of approximately 20% despite all of the usual measures aimed at securing compliance. Seven IDDM patients ranging in age from 11 to 19 years were managed in our clinic with all of our usual modalities, but all remained in long-term poor control during the 6 months immediately prior to the study. To ensure that each patient would serve as his/her own control, no changes were made in his/her management other tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…For example, hypnotic suggestions as well as OT may influence the quality of relational interactions (Banyai, 1985;Ditzen et al, 2009), the level of trust (Alladin, 2007;Kosfeld, Heinrichs, Zak, Fischbacher, & Fehr, 2005), and the strength of collaborative alliances (Esch & Stefano, 2005a, 2005bRatner, Gross, Casas, & Castells, 1990). In addition, clinical hypnosis and OT are thought to have an effect on pregnancy (Halfon, 2007;Russell, Leng, & Douglas, 2003), pain threshold (Gimpl & Fahrenholz, 2001;Montgomery, DuHamel, & Redd, 2000), inflammatory reactions (Hoareau, 1992;Petersson, Lundeberg, Sohlström, Wiberg, & Uvnäs-Moberg, 1998), and immunology (Geenen et al, 2000;Wood et al, 2003).…”
Section: Commonalities and Points Of Contactmentioning
confidence: 99%
“…For example, hypnotic suggestions as well as OT may influence the quality of relational interactions (Banyai, 1985;Ditzen et al, 2009), the level of trust (Alladin, 2007;Kosfeld, Heinrichs, Zak, Fischbacher, & Fehr, 2005), and the strength of collaborative alliances (Esch & Stefano, 2005a, 2005bRatner, Gross, Casas, & Castells, 1990). In addition, clinical hypnosis and OT are thought to have an effect on pregnancy (Halfon, 2007;Russell, Leng, & Douglas, 2003), pain threshold (Gimpl & Fahrenholz, 2001;Montgomery, DuHamel, & Redd, 2000), inflammatory reactions (Hoareau, 1992;Petersson, Lundeberg, Sohlström, Wiberg, & Uvnäs-Moberg, 1998), and immunology (Geenen et al, 2000;Wood et al, 2003).…”
Section: Commonalities and Points Of Contactmentioning
confidence: 99%
“…There were 13 studies in which the interventionist primarily worked one-to-one with the adolescent, 55,82,85,86,88,90,99,100,110,122,123,125,132 and 33 studies in which the intervention mostly took place in a group setting. 56,58,59,73,81,83,84,87,92,93,95,96,98,[102][103][104][105][106][107][108][109][111][112][113][117][118][119][120][121]126,127,131,133 Of the remaining studies, the interventions took place in family units, 59,60,97,…”
Section: Individual Versus Group Educationmentioning
confidence: 99%
“…Therefore, interventions that target hard-tomanage adolescents are of special interest. Effective initiatives could have higher cost-savings but may be more difficult to achieve with this patient group and thus require a higher commitment of resources.Twelve studies focused on poorly controlled subjects and mostly used interventions 57,88,94,[122][123][124]131 and the other five recorded improvements in a variety of behavioural or psychosocial outcomes, 56,86,97,116,134 only two of these studies showed significantly reduced hospitalisations following intervention. 94,116 Collectively, these studies illustrate that poorly controlled subjects can be assisted by tailored interventions, but they do not provide robust evidence of the cost-effectiveness of such approaches.…”
mentioning
confidence: 99%
“…89 Patients with diabetes can be treated safely with biofeedback-assisted relaxation as long as daily SMBG is maintained and medication changes are not made without physician consultation. 80 The basic premise underlying the use of relaxation therapies in diabetes is that psychologic stress has an influence on BG levels. Passive relaxation involves concentration on words or phrases designed to produce the state of relaxation, whereas progressive relaxation or active relaxation consists of sequential tensing and relaxation of specific muscle groups.…”
Section: Biofeedbackmentioning
confidence: 99%